IMPLEMENTASI PROGRAM TAHFIDZ AL-QUR’AN DALAM MEMBENTUK KARAKTER DISIPLIN DAN TANGGUNG JAWAB DI MI AL FURQON - Saeful Bahri Alamsyah Putra; Siti Qomariyah; Faisal Hamdi; Muhammad Helmi Alfian; Dede Suhendar (STKIP Subang, 2026)
Character education in Islam aims to develop students who are faithful, disciplined, and responsible. One of the efforts made by madrasahs to instill these values is through the Tahfidz Al-Qur’an program. This study aims to examine the implementation of the Tahfidz Al-Qur’an program and its role in shaping students’ discipline and responsibility at MI Al Furqon. This research employed a qualitative approach with a descriptive method. The research subjects consisted of the principal, Tahfidz teachers, and students. Data were collected through observation, interviews, and documentation. Data analysis followed the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. Data validity was ensured through source and method triangulation. The results show that MI Al Furqon integrates the national curriculum with Islamic education through its vision and mission, which emphasize the development of Qur’anic character. The Tahfidz Al-Qur’an program is implemented in a structured manner using the talaqqi, sima’an, and tikrar methods, supported by regular schedules and periodic evaluations. This program plays a positive role in developing students’ discipline through punctuality and adherence to memorization targets, as well as fostering responsibility by encouraging students to consistently maintain and review their memorization. The challenges encountered include differences in students’ memorization abilities, limited instructional time, and insufficient parental involvement. These challenges are addressed through additional mentoring, the provision of dedicated Tahfidz time, and improved communication with parents.